Kompetensi Information and Communication Technology Utilization dan Job Enrichment/Job Enlargement Meningkatkan Kinerja Pendidik dan Tenaga Kependidikan - Aditya Chandra Setiawan; Amrozi Khamidi; Nunuk Hariyati; Ellena Ihza Katerina; Cahyo Febri Wijaksono (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2022)
Abstract: The shift in working habits from home to returning to work in the office has resulted in significant changes that require readjustment. This study aims to analyze the competence of information and communication technology utilization and job enrichment/job enlargement on the performance of educators and education staff. This research uses the descriptive-correlational quantitative method. The approach in this research is made deductively. The data collection method used is primary data (directly). The instrument used is a questionnaire. The total population in this study were 114 respondents, while the sample was 95. The research sampling technique used proportional random sampling. The data analysis used is descriptive and multiple linear regression. The results of this study are, first, ICT competence, job enrichment/job enlargement received by educators and education staff and the performance of educators and education personnel at the level of the ‘high’ category. Second, there is an influence of ICT utilization competence on the performance of educators and education personnel in the era of the new average education. Third, there is the effect of job enrichment/job enlargement (JE/JE) on the performance of educators and education staff in the era of the new average education. Fourth, there is a simultaneous influence of ICT utilization and job enrichment/job enlargement (JE/JE) competencies on the performance of educators and education personnel in the era of new typical education. Abstrak: Pergesaran kebiasaan kerja dari rumah menjadi kembali kerja di kantor menimbulkan perubahan yang cukup signifikan sehingga perlu adanya penyesuaian kembali. Tujuan penelitian ini yaitu menganalisis kompetensi information and communication technology utilization dan job enrichment/job enlargement terhadap kinerja pendidik dan tenaga kependidikan. Penelitian ini menggunakan metode kuantitatif deskriptif-korelasional. Pendekatan dalam penelitian ini dilakukan secara deduktif. Metode pengumpulan data yang digunakan yaitu melalui data primer (secara langsung). Instrumen yang digunakan yaitu kuesioner. Jumlah populasi dalam penelitian ini sejumlah 114 responden, sedangkan sampel sejumlah 95 responden. Teknik sampling penelitian menggunakan proportional random sampling. Analisis data yang digunakan yaitu deskriptif dan regresi linier berganda. Hasil penelitian ini yaitu pertama, kompetensi ICT, job enrichment/job enlargement yang diterima oleh pendidik dan tenaga kependidikan dan kinerja pendidik dan tenaga kependidikan pada tingkat kategori ‘tinggi’. Kedua, terdapat pengaruh kompetensi ICT utilization terhadap kinerja pendidik dan tenaga kependidikan pada era new normal education. Ketiga, terdapat pengaruh job enrichment/job enlargement (JE/JE) terhadap kinerja pendidik dan tenaga kependidikan pada era new normal education. Keempat, secara simultan terdapat pengaruh kompetensi ICT utilization dan job enrichment/job enlargement (JE/JE) terhadap kinerja pendidik dan tenaga kependidikan pada era new normal education.